Good response to rectal diazepam in refractory cases of cyclic vomiting: A case‐series and review of the literature - Mansoureh Togha; Mahsa Babaei; Melika Jameie (Clinical Case Reports, 2023)
Key Clinical Message Although increasing in number, cases of CVS are being frequently misdiagnosed and many are refractory to the available treatments. This paper draws attention to a timely consideration of this disorder upon suspicion and proposes rectal diazepam and cinnarizine as highly effective treatments in refractory cases of CVS. Abstract Cyclic vomiting syndrome (CVS) is a set of recurrent episodic attacks of nausea and vomiting. This is a migraine‐related disorder that mostly affects children. Several medications have been recommended for abortive and prophylactic treatment. Unfortunately, in some cases, the treatment is not completely effective and affects the quality of life of the sufferer. In this paper, we report on two cases of children experiencing refractory CVS attacks who were not responsive to recommended medications for acute phase and prophylaxis. This account highlights the efficacy of rectal diazepam for the acute phase of CVS and cinnarizine, an anti‐migraine and anti‐histamine agent, for prophylaxis of further attacks.